Screening of strawberry (Fragaria × ananassa Duch.) cultivars for drought tolerance based on physiological and biochemical responses under PEG-induced stress - Attar, Şule Hilal; Ayvaz Sonmez, Duygu; Akbari, Azam; Ergün, Doğan; Bilgin, Ömer Faruk; Yeşil, Betül; Bozkurt, Merve Onur; Daşgan, Hayriye Yıldız; İkiz, Boran; Kafkas, Salih; Mezzetti, Bruno; Kafkas, Nesibe Ebru (Frontiers in Plant Science, 2025)
Climate change-driven water scarcity poses increasing challenges to strawberry production worldwide. This study evaluated drought tolerance mechanisms in fifteen strawberry (Fragaria × ananassa Duch.) cultivars in the first year and seven selected cultivars in the second year, including Turkish local varieties, using polyethylene glycol (PEG)-induced drought stress in controlled greenhouse conditions. Key physiological and biochemical parameters were assessed, including relative water content (RWC), chlorophyll content, Photosynthetic Quantum Yield, leaf dry matter content (LDMC), sugar composition, and antioxidant capacity. Drought stress significantly reduced RWC by 13.1% in year one and 7.5% in year two, while chlorophyll content declined by 4.8% and 6.6%, respectively. Photosynthetic Quantum Yield decreased by 7.9% and 12.2% across the two years. Conversely, LDMC increased by approximately 16% in both years, indicating morphological adaptation to water deficit. The most striking response was carbohydrate accumulation, particularly in year one, where total sugar content in 'Sweet Charlie' increased from 3.48% to 28.42%, and 'Monterey' showed an increase from 2.69% to 22.90%. Year two exhibited more moderate sugar responses but stronger correlations between sugar content and RWC (glucose: r = 0.93), suggesting refined osmotic adjustment mechanisms. Antioxidant activity increased across all genotypes under stress, with 'Festival' and 'Sabrina' achieving over 90% antioxidant activity. Principal component analysis and hierarchical clustering effectively discriminated drought-tolerant from sensitive cultivars. 'Brilliance' demonstrated superior drought tolerance, maintaining high RWC (89.2%) and stable sugar metabolism under stress conditions. In contrast, 'Calderon' and 'Plared' showed significant declines in physiological performance. The study reveals cultivar-specific drought response strategies, with sugar accumulation, chlorophyll stability, and antioxidant capacity serving as reliable screening markers. The identified physiological benchmarks and tolerant genotypes ('Brilliance', 'Festival', 'Sweet Charlie', and local variety 'Arnavutkِy') provide valuable resources for breeding programs targeting enhanced drought resilience. These findings contribute to understanding strawberry adaptation mechanisms under water stress and offer practical tools for sustainable production in water-limited environments.